Renal and Adrenal Ultrasonography: a valuable diagnostic tool in the salt‐wasting infant. (4th November 2015) - Reynolds, Ben Christopher; Schenk, Daniel; Kambalimath, Manjunath; Jackson, Michael; Cheetham, Tim
Abstract: The major differential diagnosis in 'salt‐wasting' infants (characterised by hyponatraemia and hyperkalaemia) is that of an adrenal or renal disorder. Appropriate management relies on rapid diagnosis, but existing guidelines do not highlight the role of ultrasonography. We describe how ultrasound may lead to a more rapid diagnosis in disorders of sex development (DSD) and other potential 'salt‐wasting' infants. Conclusion: Ultrasonography as a diagnostic tool in infants with salt‐wasting or DSD needs to be more widely recognised.